Multicentre study conducted across centres in the USA, Europe and Australia to assess the safety and effectiveness of a bilateral hypoglossal nerve stimulation system for the treatment of obstructive sleep apnoea in adults: a protocol for a pivotal, multicentre, open-label, single-arm study - B Tucker Woodson; Maria V Suurna; M Boyd Gillespie; Tod C Huntley; Melyssa Hancock; Angela Santos; Jeyakumar Subbaroyan; Fatima Makori; Grégoire Fesneau; Clemens Heiser; David T Kent (BMJ Open)
Introduction Obstructive sleep apnoea (OSA) is characterised by blood oxygen desaturations and sleep disruptions manifesting undesirable consequences. Existing treatments including oral appliances, positive airway pressure (PAP) therapy and surgically altering the anatomy of the pharynx have drawbacks including poor long-term adherence or often involving irreversible, invasive procedures. Bilateral hypoglossal nerve stimulation (HNSBL) is a new treatment for managing OSA, and this study is intended to determine whether an HNSBL system is a safe and effective treatment option for adults with OSA.Methods and analysis This is a pivotal, multicentre, prospective, single-arm study of HNSBL in PAP-intolerant adults with moderate to severe OSA. The device is activated 2 months after implantation with stimulation settings optimised before the final 12-month sleep study. At 12 months, the two coprimary effectiveness endpoints are the percentage of responders based on reduction in the Apnoea-Hypoponea Index, with hypopnoeas associated with 4% oxyhaemoglobin desaturation, and the Oxygen Desaturation Index, using drops in oxygen concentration >4% from baseline (ODI4). Secondary effectiveness endpoints include mean changes in quality-of-life assessments (daytime sleepiness and its effect on activities of daily living, OSA-specific quality of life, daytime sleepiness), levels of intermittent hypoxia, change in hypoxaemic burden and OSA severity.Ethics and dissemination The Food and Drug Administration, Advarra Institutional Review Board (IRB), University of Tennessee HSC IRB, University of Pennsylvania IRB, Weill Cornell Medicine IRB, Medical College of Wisconsin/Froedert Hospital, Human Research Protections Programme Vanderbilt University, St. Vincent’s Hospital Melbourne Human Research Ethics Committee, Ethisch Comite Universitair Ziekenhuis Antwerpen and Technische Universitat Munchen reviewed and approved this protocol. Study results will be disseminated through journal publications, updates to ClinicalTrials.gov and the Nyxoah website, and presentations at meetings and conferences.Trial registration number NCT03868618.